2022
DOI: 10.1021/acsomega.2c05581
|View full text |Cite
|
Sign up to set email alerts
|

Simulation Study on the Corrugated Plate Gas–Liquid Separator with the Assistance of the Drainage Hook

Abstract: Corrugated plate separators are widely used in the field of gas−liquid separation because of their excellent separation performance. The separation effect is very sensitive to the internal auxiliary structure of drainage hooks, so it is extremely important to study the action principle of drainage hooks to optimize the performance of corrugated plate separators. In this paper, Fluent is used as the solver and the realizable k−ε model is used to compare the separation performance of unhooked, single-hooked, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…The elongation at break reached 11.57%, which was 14.13% higher than unmodified. The improvement of mechanical properties indicated that microcrystalline cellulose and epoxy resin networks were well miscible 22 . Figure 1D shows the tensile stress–strain curves of different ratios of MCC/EP.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The elongation at break reached 11.57%, which was 14.13% higher than unmodified. The improvement of mechanical properties indicated that microcrystalline cellulose and epoxy resin networks were well miscible 22 . Figure 1D shows the tensile stress–strain curves of different ratios of MCC/EP.…”
Section: Resultsmentioning
confidence: 99%
“…The improvement of mechanical properties indicated that microcrystalline cellulose and epoxy resin networks were well miscible. 22 Figure 1D shows the tensile stressstrain curves of different ratios of MCC/EP. After adding MCC, under the same stress conditions, the strain of the composite material increased, indicating an increase in toughness.…”
Section: Mechanical Properties Of Ep Compositesmentioning
confidence: 99%
“…All these demonstrate the toughness of the epoxy resin is increased with the increase of nano sphere content. These may be because the PU nano spheres dispersed in epoxy resin can absorb the impact energy and deformation of the spheres appear, which makes the fracture surface more rough and epoxy resin more tough 30,31 …”
Section: Resultsmentioning
confidence: 99%
“…In the context of toughening in polymer blends, a highly stressed region near the equator is beneficial to endow the glassy polymer with toughness, as the crazes that emanate in a radial direction from the interface tend to be more stable, with craze initiation stress lower than crazes that appear at the pole of the particle, which tend to bend toward the direction perpendicular to the applied load as they propagate deeply into the matrix 19,20 . Micromechanics‐based FEA of epoxy resin toughened by rubber spheres showed that maximum stress concentration is found at the interface at the equator of the sphere, the whole particle is in uniform pure hydrostatic tension, the magnitude of stress within the particle is relatively low when compared to the matrix, and stress is uniform throughout the sphere 43,44 . Since the stress field in the rubber‐toughened polymers is similar to the one observed for PLA/TS blends, it is presumed that the TS particles have the potential to endow the PLA matrix with toughness independently of the degree of interfacial adhesion, as long as the size of TS particle is proper for craze initiation.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, even though the TS spherical particles have the potential to stabilize the crazes (since stress is concentrated in the equatorial plane 19,20,30,43,44 ) and endow PLA with toughness independently of the degree of interfacial adhesion, an important restriction to dispersing the TS phase in the form of droplets throughout the entire sample and developing dense crazing, is given by the volume fraction. Available literature dealing with PLA/TS blends has confirmed that plasticized TS can result in a reasonable dispersity of TS in PLA matrix, with TS particles nearly spherical when the TS wt.% is lower than 30 with particle size in the range ~1–20 μm.…”
Section: Resultsmentioning
confidence: 99%